Research Waves - Mariagiovanna Baccara; Gilat Levy; Ronny Razin (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Competing research waves start and grow as scientists choose their specialization driven by career incentives. We build a strategic experimentation framework where agents irreversibly choose between two risky fields, and information arrives faster as more agents specialize in a field. In the "bad news" case, if no news arrives, all agents join a bandwagon wave into one field. In the "good news"' case, both fields are explored in two sequential surges, followed by slow entry into the initially inferior field. We describe how the equilibrium depends on the information-production technology, and assess the impact of first-mover advantages, congestion, and deadlines.
Keywords: D7; 330; strategic experimentation; research specialisation